Analisis Kemampuan Penalaran Matematis Siswa dalam Menyelesaikan Soal Cerita Operasi Hitung di Sekolah Dasar - Miftahul Riska Nelzon; Salmaini Safitri Syam; Chandra Chandra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Mathematical reasoning ability is one of the important mathematics learning objectives to be achieved by students in schools because it involves logical and systematic thinking processes to analyze and solve mathematical problems. However, in reality, there are still many students who have difficulty in solving mathematical problems in the form of story problems. This study aims to analyze students' mathematical reasoning abilities in solving arithmetic operation story problems in elementary schools. The type of research used is descriptive qualitative research. The subjects of the study consisted of five grade II elementary school students. Data collection techniques used were observation, interviews, tests, and documentation. The results of the study showed that four students had very good reasoning abilities in solving story problems, while one student was included in the good category in solving story problems.